Karakteristik Kimia Lahan Kering dan Rekomendasi Pemupukan Pertanaman Kedelai di Kabupaten Bengkulu Selatan - Tri Wahyuni; Taupik Rahman; Irma Calista Siagian (Seminar Nasional Lahan Suboptimal, 2018)
Wahyuni et al, 2019. Dry Land Chemical Characteristics and Soybean Fertilizer Recommendation in Bengkulu Selatan District. pp. 32-36.Land characteristics plays an important role for crop cultivation as the basis needed to determine the soil fertility of agricultural land. Soil fertility is the basis for determining fertilizer recommendations. This objective of this research was to assess the chemical characteristics of South Bengkulu Regency dry land and fertilizer recommendations for soybean cropping. Dry land sampling was taken from South Bengkulu Regency and sample was analyzed at the Bengkulu AIAT Soil Laboratory in 2015. The soil acidity are varied according to the position on the landscape in South Bengkulu Regency from acidic to sour (80% to 20%). Organic content are varied from very low to high level (68 to 4 %). potential K content is very low (100%) and potential P content was varied from very low to low( 96 to 4 %).  Therefore, the appropriate fertilization recommendations should be undertaken to improve soil fertility and yield potential include 1) liming 1-2 tons / ha and using N fertilizer in the form of urea, 2) adding organic matter 2 t / ha, 3) 150 kg KCl fertilizer / ha, and 4) SP-36 fertilizer 200 kg / ha.